Peran Literasi Keuangan terhadap Kinerja Keuangan UMKM dengan Pemanfaatan FinTech sebagai Variabel Moderasi di Provinsi Jawa Barat - Rachman, Bobi; Dewi, Fertika Puspita; Susanto, Laela (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the effect of financial literacy on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) with the utilization of Financial Technology (FinTech) as a moderating variable. The research is grounded in the importance of MSME actors’ ability to manage finances effectively and utilize digital innovation to enhance business competitiveness and sustainability in the digital economy era. A quantitative explanatory approach was employed, involving MSME owners in West Java Province as the study population, with a sample of 400 respondents determined using the Slovin formula at a 5% margin of error. Data were collected through Likert-scale questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings show that financial literacy has a positive and significant effect on MSME financial performance, as indicated by an R² value of 0.582. This means that 58.2% of the variation in financial performance is explained by financial literacy and FinTech utilization, while the remaining 41.8% is influenced by other factors outside the model. Moreover, FinTech utilization also has a positive effect on financial performance and moderates the relationship between financial literacy and financial performance. Higher FinTech adoption strengthens the influence of financial literacy on MSME performance. These findings highlight the importance of synergy between financial education and digital technology adoption in promoting financial inclusion and supporting MSME growth in West Java.